2016
DOI: 10.1159/000447337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of XRCC1, GSTP1, and GSTM1 Polymorphisms on the Survival of Ovarian Carcinoma Patients Treated with Chemotherapy

Abstract: Background: Single nucleotide polymorphic variants of DNA repair genes may improve drug efficacy through altering expression levels of the encoded proteins. This study evaluated the influence of genetic polymorphism GSTP1 Ile105Val, GSTM1 (null/non-null) and 2 XRCC1 polymorphisms (Arg194Trp and Arg399Gln) on the survival of ovarian carcinoma patients treated with chemotherapy. Methods: 106 patients received treatment with a carboplatin-based or alternative chemotherapy. Polymorphisms were genotyped by pyrosequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
10
2
Order By: Relevance
“…Several studies have reported the impact of XRCC1 polymorphisms Arg194Trp, Arg280His, and Arg399Gln on OS in OC receiving platinum-based chemotherapy. However, these results were not consistent, [ 17 21 ] with some studies indicating that these polymorphisms could improve OS, while others have reported differently. Thus, this study performed a meta-analysis summarizing the available data to investigate the impact of Arg399Gln, Arg194Trp, and Arg280His polymorphisms on the OS of OC patients receiving platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Several studies have reported the impact of XRCC1 polymorphisms Arg194Trp, Arg280His, and Arg399Gln on OS in OC receiving platinum-based chemotherapy. However, these results were not consistent, [ 17 21 ] with some studies indicating that these polymorphisms could improve OS, while others have reported differently. Thus, this study performed a meta-analysis summarizing the available data to investigate the impact of Arg399Gln, Arg194Trp, and Arg280His polymorphisms on the OS of OC patients receiving platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 63%
“…Twenty-five studies were discarded at the stage of full text review. Among the remaining 14 citations, 5 studies were finally identified and included for analysis [ 17 21 ] ; the rest of them were excluded for the following reasons: incomparable data, nonrelevant genotypes, and focus on other outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of XRCC-1 Arg194 polymorphism on clinical outcome has been studied for NSCLC, prostate, and ovarian cancers. [22][23][24] The impact of the XRCC-1 Arg194Trp SNP lacks in LALSCC, and it is difficult to apply the clinical outcome of different types of cancer to LALSCC, as the treatment strategy used is different from one another. The study by Nanda et al, in HNSCC reported the 2-year PFS, OS, and LFFS of polymorphic variant compared with the wild variant as 57.0% vs 42.2% (P-.077), 73.0% vs 55.5% (P-.14), and 45.1% vs 58.6% (P-.09), which is in accordance to our study.…”
Section: Discussionmentioning
confidence: 99%
“…21 Studies were carried out to estimate the bio-predictive role of XRCC-1 SNPs for the clinical outcome of a lung, prostate, ovarian cancer, and HNSCC, but data regarding HNSCC are limited. [21][22][23][24][25] In this present study, we have studied XRCC-1 Arg194Trp polymorphism as a bio-predictor for ARIT in LALSCC undergoing CRT, and we hypothesize that patients with the polymorphic variant will have a higher ARIT and better response to CRT.…”
mentioning
confidence: 99%
“…6,7 The 10-year progression-free survival rate of recurrent patients is less than 15%. 2 Over the past 50 years, many drug resistance associated genes such as CTR1, GSTP1, ERCC1, XIAP and NT5E, [8][9][10][11][12] involving in drug transport, DNA repair, and drug transformation had been intensively studied. [13][14][15][16] However, no powerful genes have been identified so far.…”
Section: Introductionmentioning
confidence: 99%